Fisheries: Fisheries support estimates (Edition 2016) (OECD Agriculture Statistics, 2016)
This dataset presents information on fisheries policies. It is designed to monitor and quantify developments in fisheries policy, to establish a common basis for policy dialogue among countries, and to provide economic data to assess the effectiveness and efficiency of policies. The dataset report country programmes data aggregated according to the main indicators presented in the Fisheries Support Estimate Manual